STUDI VARIASI FRAKSI BERAT TERHADAP KEKUATAN TARIK GLASS FIBER REINFORCED POLYMER HYBRID SABUT KELAPA - Setiajit, Sahid Bayu; Permana, Indra; Ikhsan, Muhammad (Teknika, 2024)
This research is about studying a hybrid composite that combines synthetic and natural fibres to achieve optimal strength while utilizing natural fibres, which are abundant on the Indonesian coast. The synthetic fibre used in this research is glass fiber in the form of woven roving, while the natural fibre uses coconut fibre in the form of a mat. The use of glass fibre, which is known to be strong and has good flexibility, aims to improve the mechanical properties of coconut fibre. Hybrid composites are made using the hand lay-up method with a Glass Fiber/ Coconut Fiber / Glass Fiber [GF/SK/GF] layer arrangement. Weight fractions are varied to find the optimum weight fraction that produces a hybrid composite with the best tensile strength. Composite specimens were made and subjected to tensile tests following ASTM D-638 standards. The test results show that the average strength of this hybrid composite is 46 MPa with an elastic modulus of 1029 MPa. The optimum weight fraction for this composite is 11% glass fibre, 19% coconut fibre, and 70% resin, producing a tensile strength of 56 MPa.